Domestic gardens play a dominant role in selecting alien species with adaptive strategies that facilitate naturalization. Issue 5 (28th January 2019) - Guo, Wen‐Yong; van Kleunen, Mark; Pierce, Simon; Dawson, Wayne; Essl, Franz; Kreft, Holger; Maurel, Noëlie; Pergl, Jan; Seebens, Hanno; Weigelt, Patrick; Pyšek, Petr
Abstract: Aim: Horticulture has been recognized as the main pathway of plant invasions worldwide. The selection of ornamental garden plants is not random, and certain plant characteristics related to adaptive plant strategies are preferred by horticulture and may promote invasion. We examined the direct and indirect interactions between horticultural use, species adaptive strategies (competitive (C), stress‐tolerant (S), and ruderal (R)), native range size and naturalization success. Location: Global. Time period: From 1492 to the present. Major taxa studied: Vascular plants. Methods: We compiled a dataset of 3, 794 plant species including their C‐, S‐ and R‐scores, native range size, cultivation in botanic and domestic gardens and whether the species is naturalized in at least one region globally (naturalization incidence). For the 1, 711 naturalized species, we also calculated naturalization extent, that is, the number of regions where the species has naturalized. We used phylogenetic path analysis to disentangle the direct and indirect effects of all variables on both naturalization incidence and extent, and the relationships between variables. Results: Approximately 87 and 94% of the 1, 711 naturalized species were cultivated in botanic or domestic gardens, respectively, compared to c . 55 and 50% of the 2, 083 non‐naturalized species, respectively. We found a cascading structure among the examined variables: (a) species exhibiting C‐ or R‐selected strategies and having large native ranges tended to be cultivated in domestic and botanic gardens, became naturalized outside their native ranges and occupied more regions in their naturalized ranges; (b) C‐, S‐ and R‐scores also had indirect effects on naturalization success, which were mediated by horticultural use and native range size; and (c) cultivation in domestic gardens was the strongest factor examined that could explain plant species' naturalization success. Main conclusions: We show that horticulture is not only the major introduction pathway of alien plants, but also that in particular domestic gardens select species predisposed to invade and naturalize.